Asphalt-based porous hard carbon material prepared with assistance of chloride addition and preparation method of asphalt-based porous hard carbon material

By adding chloride to the asphalt-based hard carbon precursor and sintering at high temperature, porous hard carbon materials with high capacity and excellent rate performance were prepared, which solved the problems of cumbersome process, high cost and poor sodium ion storage performance in the prior art, and achieved more efficient sodium ion storage and battery performance improvement.

CN119551652APending Publication Date: 2025-03-04NORTHEASTERN UNIV CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411718662.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, hard carbon materials prepared with asphalt as raw materials are cumbersome, with high costs and poor sodium ion storage performance, making it difficult to meet the needs of large-scale applications of sodium ion batteries.

Method used

By adding a quantitative amount of chloride to the reaction system of the asphalt-based hard carbon precursor, and performing mechanical grinding and high-temperature sintering, a chloride-assisted production of asphalt-based porous hard carbon negative electrode material with higher capacity and better rate performance is prepared.

Benefits of technology

This method successfully suppressed the graphitization trend of asphalt, formed an amorphous hard carbon structure, improved the transmission efficiency of sodium ions, significantly improved the rate performance and cycling performance of the battery, and at the same time reduced production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005157484560000011
    Figure HDA0005157484560000011
  • Figure HDA0005157484560000012
    Figure HDA0005157484560000012
  • Figure HDA0005157484560000021
    Figure HDA0005157484560000021
Patent Text Reader

Abstract

The invention relates to an asphalt-based porous hard carbon material prepared under assistance of chloride addition and a preparation method of the asphalt-based porous hard carbon material, and belongs to the field of alkali metal ion battery negative electrode materials. The method aims at solving the problems that an existing treatment method for preparing a hard carbon material by taking asphalt as a raw material is tedious and high in cost. The preparation method of the asphalt porous hard carbon material comprises the following steps: mixing hard carbon precursors (pure asphalt, pre-oxidized asphalt, pre-carbonized asphalt and the like) and chloride according to a ratio, and synthesizing a sample through a solid sintering method. According to the hard carbon material, a large number of micropores and mesopores of 2 nm and below are introduced into a carbon matrix of the hard carbon material to serve as storage point locations of sodium ions, so that the hard carbon negative electrode material with a highly disordered structure is obtained, higher capacity and rate capability (219-350 mAh g <-1 >) are obtained, the first-circle coulombic efficiency is 70-80% under the current density of 2Ag <-1 >, and the capacity retention rate is 70-78% after 400 cycles. According to the preparation method, the charge-discharge capacity and the cycling stability of the hard carbon material can be improved, and asphalt is adopted as a hard carbon precursor and is rich in source and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a chloride-added asphalt-based porous hard carbon material and a preparation method thereof, and belongs to the field of negative electrode materials for alkali metal ion batteries. Background Art

[0002] With the increasing demand for energy, secondary batteries have received widespread attention in the field of large-scale energy storage systems and electric vehicles. Currently, lithium-ion batteries have problems such as low lithium reserves and high costs, which make it difficult to meet future market demand. Due to their low cost and abundant natural reserves, sodium-ion batteries have been widely regarded as a powerful supplement to lithium-ion batteries in the field of electric vehicles, especially in the field of large-scale stationary energy storage. More importantly, the production equipment of sodium-ion batteries is fully compatible with that of lithium-ion batteries, which makes the existing lithium-ion battery infrastructure suitable for large-scale production of sodium-ion batteries.

[0003] Carbonaceous anodes are favored as anode materials for sodium-ion batteries due to their low cost and simple preparation process. Unfortunately, graphite, used as anode for commercial lithium-ion batteries, is chemically deactivated when storing sodium ions due to its small interlayer spacing and inability to generate stable Na-C intercalation compounds, and has been proven to be unsuitable for sodium-ion batteries. Therefore, it is necessary to develop a fast Na + High-performance all-carbon anode materials with both good storage capacity and long cycle life remain challenging.

[0004] At present, the negative electrode materials widely used in sodium-ion batteries are mainly two amorphous carbon materials: hard carbon and soft carbon. The precursor raw materials of hard carbon materials are generally biomass or artificial synthetic resins. The resulting products have many performance advantages such as high sodium storage capacity, low sodium storage voltage, and good cycle performance, but they are expensive and have low carbon yields. The precursor raw materials of soft carbon are usually lower in cost, have a more ordered structure, fewer defects and shorter interlayer spacing, and their specific capacity is often lower than that of hard carbon. The carbon layer arrangement regularity of hard carbon materials is lower than that of soft carbon materials, and more micropores can be formed between their layers to facilitate the insertion and extraction of sodium ions. It is the current preferred negative electrode material for sodium-ion batteries. The current bottleneck of its industrialization is mainly the inability to find cheap precursor raw materials suitable for large-scale mass production.

[0005] In terms of raw material prices, carbon yield, production price and cost-effectiveness, pitch composed of various aromatic fused rings represents a potential precursor to produce cost-effective carbon anodes for sodium-ion batteries. However, pitch has the properties of a soft carbon precursor, which allows the condensation and rearrangement of aromatic cores and side chains during liquid carbonization to stack nearly parallel carbon sheets together. Therefore, the development of a pitch-based hard carbon negative electrode material with a simple preparation process, higher sodium storage efficiency, and low cost and stability is of great significance for the large-scale application of sodium-ion batteries. Summary of the invention

[0006] In order to solve the technical problems that the current hard carbon materials prepared with asphalt as raw material have complicated processes, high costs and poor sodium ion storage performance, the present invention provides a method for preparing asphalt-based hard carbon materials with the assistance of chloride, which is applied to negative electrode materials of sodium ion batteries. The present invention adds a quantitative chloride to the reaction system of the asphalt-based hard carbon precursor, and uses mechanical grinding and mixing to form a high-temperature sintering to form a chloride-assisted asphalt-based porous hard carbon negative electrode material with higher capacity and better rate performance. The asphalt-based porous hard carbon negative electrode material prepared with the assistance of chloride not only successfully inhibits the graphitization of asphalt to form an amorphous hard carbon structure, but also forms a large number of micropores and mesoporous structures of 2nm and below in the material, which not only improves the sodium ion transmission efficiency, but also greatly improves the rate performance and cycle performance of the battery.

[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0008] A chloride-added asphalt-based porous hard carbon material is prepared, wherein the material is a hard carbon material that obtains a more porous structure with the assistance of chloride.

[0009] The chloride-assisted preparation of the asphalt-based carbon material of the present invention successfully inhibits the graphitization tendency of the asphalt, so that it forms an amorphous hard carbon structure.

[0010] The porous hard carbon material of the present invention has a rich porous structure, and the pore size thereof is mainly composed of micropores of about 2 nm and mesopores of micrometer size.

[0011] Furthermore, the present invention proposes for the first time to prepare asphalt-based hard carbon materials by adding chlorides as an auxiliary, and to use chlorides as inhibitors and pore-forming agents to inhibit the high-temperature graphitization trend of the asphalt-based carbon materials and make the hard carbon materials present a porous structure.

[0012] The method is simple to operate, easy to control, has a short process flow, low cost, and is easily applicable to the industrial production of asphalt-based hard carbon.

[0013] Another object of the present invention is to provide the above-mentioned chloride-assisted preparation method of asphalt-based porous hard carbon negative electrode for sodium ion battery.

[0014] A method for preparing a chloride-assisted asphalt-based porous hard carbon negative electrode for a sodium ion battery comprises the following steps: mixing an asphalt-based carbon precursor and a chloride in proportion and grinding them sufficiently; then calcining the mixture at a high temperature in an inert gas; after the sample is cooled to room temperature with the furnace, taking out the sample, and obtaining a chloride-assisted asphalt-based porous hard carbon negative electrode material.

[0015] Preferably, the asphalt-based carbon precursor is pure asphalt, pre-oxidized asphalt, pre-carbonized asphalt, etc.

[0016] The present invention adds a carbon material using asphalt as a precursor into the reactants for preparation.

[0017] Preferably, the amount of asphalt added is 1-100g.

[0018] Preferably, the mass ratio of the hard carbon precursor to the chloride is in the range of 1-15.

[0019] Preferably, the pitch-based carbon precursor and the chloride are mixed by manual grinding or ball milling.

[0020] Preferably, the inert atmosphere for high temperature calcination is argon or nitrogen.

[0021] Preferably, the temperature of the high-temperature sintering is 400-1400° C., and the holding time of the high-temperature sintering is 1-48 hours.

[0022] Preferably, the high temperature sintering heating rate is 1-10°C / min, and step heating is adopted, firstly the temperature is quickly raised to a certain temperature, then the temperature is slowly raised to a certain temperature and kept at this temperature for several hours.

[0023] Another object of the present invention is to provide the use of the above-mentioned asphalt-based hard carbon material prepared by chloride-assisted addition as a negative electrode material for sodium ion batteries.

[0024] The beneficial effects of the present invention are:

[0025] (1) For the first time, asphalt-based porous hard carbon materials were successfully prepared by adding chloride to asphalt-based carbon precursors such as pure asphalt, pre-oxidized asphalt, and pre-carbonized asphalt to assist in high-temperature sintering. Taking pure asphalt as an example, the obtained material presents a porous structure with micropores with a pore size of about 2nm and mesopores of micrometer size, and exhibits a hard carbon structure with amorphous carbon, which enables sodium ions to obtain better transmission efficiency, achieve higher capacity and rate performance, and maintain good stability.

[0026] (2) The present invention attempts to improve the electrochemical properties of asphalt-based carbon materials for sodium ion batteries by preparing a sodium ion battery asphalt-based porous hard carbon negative electrode with the assistance of chloride. Due to its low manufacturing cost and simple preparation process, this material conforms to the green and economic development concept and has broad application prospects in the fields of large-scale energy storage.

[0027] (3) As a negative electrode material for sodium ion batteries, the chloride-assisted preparation of sodium ion battery asphalt-based porous hard carbon negative electrode materials exhibits higher capacity and excellent rate performance at current densities of 100 mA / g to 5000 mA / g, which is better than the currently reported asphalt-based negative electrode materials, and exhibits good cycle performance at a current density of 2000 mA / g.

[0028] (4) This method provides a chloride-assisted method for preparing asphalt-based porous hard carbon negative electrode materials for sodium ion batteries. The method is simple to operate, easy to control, has a short process flow, low cost, and is easy to use for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The X-ray diffraction patterns of the products POC and PONC of Comparative Example 2 and Example 2 are shown.

[0030] Figure 2 (a) to (d) are scanning electron microscope images of the products PC and PNC of Comparative Example 1 and Example 1.

[0031] Figure 3 (a) to (d) are scanning electron microscope images of the products POC and PONC of Comparative Example 2 and Example 2.

[0032] Figure 4 (a)(b) Rate and cycle performance diagrams of the products POC and PONC of Comparative Example 2 and Example 2.

[0033] Figure 5 (a)(b) Rate and cycle performance diagrams of the products PCC and PCNC of Comparative Example 3 and Example 3. Specific implementation plan

[0034] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0035] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0036] The basic idea of ​​the present invention is: by selecting chloride as an inhibitor and pore-forming agent to inhibit the high-temperature graphitization trend of asphalt-based carbon materials, the asphalt-based porous hard carbon negative electrode material is successfully prepared for the first time by chloride-assisted high-temperature sintering. The specific method is to mix the asphalt-based carbon precursor (pure asphalt, pre-oxidized asphalt, pre-carbonized asphalt, etc.) with the chloride in proportion and grind it thoroughly; then the mixture is calcined at high temperature in an inert gas; after the sample is cooled to room temperature with the furnace, the sample is taken out to obtain the chloride-assisted preparation of the asphalt-based porous hard carbon negative electrode material. And the sample is used for the negative electrode of the sodium ion battery, so that the sodium ion battery obtains a higher charge and discharge specific capacity and excellent rate performance.

[0037] Example 1

[0038] A method for preparing a chloride-assisted asphalt-based porous hard carbon negative electrode for a sodium ion battery, comprising:

[0039] The asphalt and chloride are mixed in a certain mass ratio and ground thoroughly; the mixture is then heated in an inert gas using a step-by-step method, first quickly heated to a certain temperature, then slowly heated to 400-1400°C and kept warm for 1-48 hours; after the sample is cooled to room temperature with the furnace, the sample is taken out to obtain a asphalt-based porous hard carbon negative electrode material, which is named PNC.

[0040] By SEM( Figure 2 c, d) It can be found that the PNC sample exhibits a fluffy porous morphology, and an obvious lamellar structure can be observed at the edge of the pores.

[0041] PNC was ground with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1, dissolved with a certain amount of N-methylpyrrolidone, coated on copper foil to form a film, dried in vacuum at a certain temperature, cut and pressed. A CR2032 button half-cell was assembled in an argon-filled glove box using a metal sodium sheet as the counter electrode, sodium hexafluorophosphate electrolyte, and a Whatman glass microfiber membrane.

[0042] Example 2

[0043] A method for preparing a chloride-assisted asphalt-based porous hard carbon negative electrode for a sodium ion battery, comprising:

[0044] The pre-oxidized asphalt sample is obtained by first heating pure asphalt to a certain temperature at a heating rate of 10°C / min in an air atmosphere, keeping it warm for a certain period of time, and cooling it to room temperature in a furnace; the pre-oxidized asphalt is mixed with chloride (mass ratio ranging from 1 to 15) and fully ground; then the mixture is heated in an inert gas by using a step-heating method, first quickly heating it to a certain temperature, then slowly heating it to 400 to 1400°C and keeping it warm for 1 to 48 hours; after the sample is cooled to room temperature in the furnace, the sample is taken out to obtain an asphalt-based porous hard carbon negative electrode material, which is named PONC.

[0045] pass Figure 2 It can be determined by XRD that, compared with the POC sample, the PONC sample shows obvious peak broadening and left shift, indicating that the POC sample has a lower degree of graphitization and a larger interlayer spacing, showing a typical hard carbon structure.

[0046] By SEM( Figure 3 c, d) It can be found that the PONC sample exhibits a fluffy porous morphology, and an obvious lamellar structure can be observed at the edge of the pores.

[0047] PONC was ground with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1, dissolved with a certain amount of N-methylpyrrolidone, coated on copper foil to form a film, dried in vacuum at a certain temperature, cut and pressed. A CR2032 button half-cell was assembled in an argon-filled glove box using a metal sodium sheet as the counter electrode, sodium hexafluorophosphate electrolyte, and a Whatman glass microfiber membrane.

[0048] The sample showed a reversible capacity of 352.09 mAh / g, and still showed a reversible capacity of 255.59 mA / g at a current density of 1 A / g, which is at the leading level among such materials. After 600 cycles at a current density of 2000 mA / g, it still maintained a capacity retention rate of 73.33% ( Figure 4 ).

[0049] Example 3

[0050] A method for preparing a chloride-assisted asphalt-based porous hard carbon negative electrode for a sodium ion battery, comprising:

[0051] The pre-carbonized asphalt sample is obtained by first heating pure asphalt and glucose to a certain temperature at a heating rate of 10°C / min under an inert gas atmosphere, keeping the temperature for a certain period of time, and cooling to room temperature with the furnace; the pre-carbonized asphalt is mixed with chloride (mass ratio range is 1 to 15) and fully ground; then the mixture is heated in an inert gas by using a step-heating method, first quickly heating to a certain temperature, then slowly heating to 400 to 1400°C and keeping the temperature for 1 to 48 hours; after the sample is cooled to room temperature with the furnace, the sample is taken out to obtain an asphalt-based porous hard carbon negative electrode material, which is named PCNC.

[0052] PCNC was ground with acetylene black and polyvinylidene fluoride (PVDF) in a ratio of 7:2:1, dissolved with a certain amount of N-methylpyrrolidone, coated on copper foil to form a film, dried in vacuum at a certain temperature, cut and pressed. A CR2032 button half-cell was assembled in an argon-filled glove box using a metal sodium sheet as the counter electrode, sodium hexafluorophosphate electrolyte, and a Whatman glass microfiber membrane.

[0053] The sample showed a reversible capacity of 345.35 mAh / g, and still showed a reversible capacity of 250.05 mA / g at a current density of 1 A / g, which is at the leading level among such materials. After 600 cycles at a current density of 2000 mA / g, it still maintained a capacity retention rate of 76.08% ( Figure 5 ).

[0054] Comparative Example 1

[0055] A method for preparing a sodium ion battery pitch-based carbon negative electrode material, comprising:

[0056] By placing pure asphalt in an inert gas and using step heating, first quickly heating it to a certain temperature, then slowly heating it to 400-1400°C and keeping it warm for 1-48 hours; after the sample is cooled to room temperature with the furnace, the sample is taken out to obtain an asphalt-based carbon negative electrode material, which is named PC.

[0057] By SEM( Figure 2 a, b) It can be found that the PC sample shows an irregular block morphology, and a regular shale-like structure can be observed at the edge of the block, showing an obvious layered structure.

[0058] PC, acetylene black and polyvinylidene fluoride (PVDF) were ground in a ratio of 7:2:1, dissolved with a certain amount of N-methylpyrrolidone, coated on copper foil to form a film, dried in vacuum at a certain temperature, cut and pressed. A CR2032 button half-cell was assembled in an argon-filled glove box using a metal sodium sheet as the counter electrode, sodium hexafluorophosphate electrolyte, and a Whatman glass microfiber membrane.

[0059] Comparative Example 2

[0060] A method for preparing a sodium ion battery pitch-based carbon negative electrode material, comprising:

[0061] The pre-oxidized asphalt sample is obtained by first heating the pure asphalt to a certain temperature at a heating rate of 10°C / min in an air atmosphere, keeping it warm for a certain period of time, and cooling it to room temperature in a furnace; the pre-oxidized asphalt is heated in an inert gas by using a step-heating method, first quickly heating it to a certain temperature, then slowly heating it to 400-1400°C and keeping it warm; after the sample is cooled to room temperature in the furnace, the sample is taken out to obtain an asphalt-based carbon negative electrode material, which is named POC.

[0062] pass Figure 2 It can be determined by XRD that, compared with the POC sample, the PONC sample shows obvious peak broadening and left shift, indicating that the POC sample has a lower degree of graphitization and a larger interlayer spacing, showing a typical hard carbon structure.

[0063] By SEM( Figure 3 a, b) It can be found that the POC sample shows an irregular block morphology, and many pits and pores appear on the block surface.

[0064] POC, acetylene black and polyvinylidene fluoride (PVDF) were ground in a ratio of 7:2:1, dissolved with a certain amount of N-methylpyrrolidone, coated on copper foil to form a film, dried in vacuum at a certain temperature, cut and pressed. A CR2032 button half-cell was assembled in an argon-filled glove box using a metal sodium sheet as the counter electrode, sodium hexafluorophosphate electrolyte, and a Whatman glass microfiber membrane.

[0065] The sample exhibited a reversible capacity of 153.24 mAh / g, a reversible capacity of 102.36 mA / g at a current density of 1 A / g, and a capacity retention rate of 78.4% after 600 cycles at a current density of 2000 mA / g. Figure 4 ).

[0066] Comparative Example 3

[0067] A method for preparing a sodium ion battery pitch-based carbon negative electrode material, comprising:

[0068] The pre-carbonized asphalt sample is obtained by first heating pure asphalt and glucose to a certain temperature at a heating rate of 10°C / min in an inert gas atmosphere, keeping it warm for a certain time, and cooling it to room temperature with the furnace; the pre-carbonized asphalt is heated in an inert gas by step, first quickly heating it to a certain temperature, then slowly heating it to 400-1400°C and keeping it for 1-48h; after the sample is cooled to room temperature with the furnace, the sample is taken out to obtain the asphalt-based carbon negative electrode material, which is named PCC.

[0069] PCC, acetylene black and polyvinylidene fluoride (PVDF) were ground in a ratio of 7:2:1, dissolved with a certain amount of N-methylpyrrolidone, coated on copper foil to form a film, dried in vacuum at a certain temperature, cut and pressed. A CR2032 button half-cell was assembled in an argon-filled glove box using a metal sodium sheet as the counter electrode, sodium hexafluorophosphate electrolyte, and a Whatman glass microfiber membrane.

[0070] The sample exhibited a reversible capacity of 163.19 mAh / g, a reversible capacity of 113.41 mA / g at a current density of 1 A / g, and a capacity retention rate of 67.37% after 600 cycles at a current density of 2000 mA / g. Figure 5 ).

Claims

1. A method for preparing a pitch-based porous hard carbon material by adding chloride, characterized in that: The hard carbon material is a hard carbon material that obtains a more porous structure with the assistance of chloride.

2. The porous hard carbon material according to claim 1, characterized in that: The porous hard carbon material has a faster sodium ion transmission rate and has higher capacity and rate performance.

3. The porous hard carbon material according to claim 1, characterized in that: The porous hard carbon material has a rich porous structure, mainly composed of micropores and mesopores of about 2 nm.

4. The porous hard carbon material according to claim 1, characterized in that: The porous hard carbon material presents a fluffy porous morphology, and an obvious flaky structure can be observed at the pore edges.

5. A method for preparing a pitch-based porous hard carbon material with the aid of chloride addition, characterized in that: The asphalt-based hard carbon precursor is mixed with chloride and ground thoroughly; the mixture is then calcined at high temperature in an inert gas for several hours and then cooled to room temperature in the furnace.

6. The preparation method according to claim 5, characterized in that: The asphalt-based hard carbon precursor may be pure asphalt, pre-oxidized asphalt, pre-carbonized asphalt, etc.

7. The preparation method according to claim 5, characterized in that: The mass ratio of the hard carbon precursor to the chloride is in the range of 1-15.

8. The preparation method according to claim 5, characterized in that: The temperature of the high-temperature carbonization is 400 to 1400° C., and the high-temperature carbonization insulation time is 1 to 48 hours.

9. The preparation method according to claim 5, characterized in that: The heating rate of the high temperature carbonization is 1-10°C / min.

10. Use of the asphalt-based porous hard carbon material according to any one of claims 1 to 4 as a negative electrode material for sodium ion batteries.

Citation Information

Cited By

  • Asphalt-based soft and hard carbon porous composite nanosheet negative electrode material and preparation method and application thereof

    CN120504309A